Upaya Meningkatkan Hasil Belajar Siswa Pada Materi Macam-Macam Gaya Melalui Model Pembelajaran Auditory, Intellectualy, Repetition (Air) di Kelas Iv Sd Negeri 4 Peudada - Faizah M. Nur; Tutiliana Tutiliana (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the increase in learning outcomes, teacher and student activities and the responses of fourth grade students at SD Negeri 4 Peudada through the Auditory, Intellectually, Repatition (AIR) learning model on various styles of material. The approach used is a qualitative approach. This type of research is class action research (classroom action research). The data used are data from cycle test results, observation results and student response questionnaire results. The source of the data in this study were fourth grade students at SD Negeri 4 Peudada. Data Collection Techniques namely Tests, Observations (observations) and Questionnaires. Based on the results of the research that there was an increase in the learning outcomes of fourth grade students at SD Negeri 4 Peudada by using the Auditory, Intellectual, Repetition (AIR) Learning model in the material of various styles, in cycle I obtained 39% complete, cycle II obtained 89% complete . The activities of teachers and students in class IV SD Negeri 4 Peudada using the Auditory, Intellectual, Repetition (AIR) Learning model in the material of various styles, namely the activities of teachers in cycle I, action I was 73%, action II was 80.5%. Cycle II action I was 87%, action II was 98% while student activities cycle I action I was 71.17% and action II 80%. Cycle II action I 87% and action II 98%. The response of fourth grade students at SD Negeri 4 Peudada by using the Auditory, Intellectual, Repetition (AIR) Learning model on the material of various styles in cycle I and cycle II, it was found that generally students strongly agreed and agreed with the learning activities in cycle I and cycle II